Reciprocal Induction of MDM2 and MYCN in Neural and Neuroendocrine Cancers - Tran, Hung N.; Singh, Hardeep P.; Guo, Wenxuan; Cambier, Linda; Riggan, Luke; Shackleford, Gregory M.; Thornton, Matthew E.; Grubbs, Brendan H.; Erdreich-Epstein, Anat; Qi, Dong-Lai; Cobrinik, David (Frontiers in Oncology, 2020)
MYC family oncoproteins MYC, MYCN, and MYCL are deregulated in diverse cancers and via diverse mechanisms. Recent studies established a novel form of MYCN regulation in MYCN-overexpressing retinoblastoma and neuroblastoma cells in which the MDM2 oncoprotein promotes MYCN translation and MYCN-dependent proliferation via a p53-independent mechanism. However, it is unclear if MDM2 also promotes expression of other MYC family members and has similar effects in other cancers. Conversely, MYCN has been shown to induce MDM2 expression in neuroblastoma cells, yet it is unclear if MYC shares this ability, if MYC family proteins up-regulate MDM2 in other malignancies, and if this regulation occurs during tumorigenesis as well as in cancer cell lines. Here, we report that intrinsically high MDM2 expression is required for high-level expression of MYCN, but not for expression of MYC, in retinoblastoma, neuroblastoma, small cell lung cancer, and medulloblastoma cells. Conversely, ectopic over-expression of MYC as well as MYCN induced high-level MDM2 expression and gave rise to rapidly proliferating and MDM2-dependent cone-precursor-derived masses in a cultured retinoblastoma genesis model. These findings reveal a highly specific collaboration between the MDM2 and MYCN oncoproteins and demonstrate the origin of their oncogenic positive feedback circuit within a normal neuronal tissue.